G05 Memory for object locations in preclinical Huntington's disease. (16th November 2010) - Frick, A; Wahlin, Å; Graff, C; Byrne, G; Robins Wahlin, T-B
Abstract : Background: Recent findings support a continuous model of slow cognitive decline in Huntington's disease (HD) starting already in the preclinical phase. Verbal memory deficits have been found in preclinical HD. However, not much is known about visuospatial memory in preclinical HD. Aim: The aim of the study was to investigate visuospatial memory in preclinical HD. Methods: Participants (n=70) were recruited through a predictive testing programme for HD. The number of CAG repeats in the expanded allele and current age were used to calculate predicted years to onset (PYTO) of HD. Three groups were formed based on genetic information and median split of PYTO: carriers with less than 12 years to disease onset (PYTO <12, n=16); carriers with 12 or more years to disease onset (PYTO ≥12, n=16); and non-carriers (n=38). Three neuropsychological tests were used to examine visuospatial ability and memory: Rey–Osterrieth Complex Figure Test, Copy and Recall after 3 min; Corsi Block-tapping Test; and an experimental Spatial Test where the participants had to memorise the position of 20 objects in a room and re-identify their locations after a 2 min delay. Results: The PYTO <12 group scored lower than the non-carriers on the Corsi Block-tapping Test (p=0.023) and on the Spatial Test (p=0.020). No significant differences were found on the Rey Complex Figure Test, or between the PYTO <12 and the PYTO ≥12 groups or between the PYTO ≥12 group and the non-carriers on any of the tests. Conclusions: The results suggest deficits in spatial episodic memory and spatial working memory in preclinical HD. These deficits are associated with visuospatial (three-dimensional) object location memory, but not with visual memory, in carriers with less than 12 estimated years to disease onset. The results are compatible with dysfunction not only in the dorsal caudate nucleus and the putamen but also in corticostriatal circuits connecting striatum with prefrontal and parietal cortices.